STUDIES ABOUT CLIMATE CHANGE IN THE TÂRNAVE AND MURFATLAR VINEYARDS - Elena-Andreea POP (Agricultura, 2020)
The temperature and precipitation are representative for the variability of the wine climate at regional level, in relation to the requirements of the varieties, influencing the quality of the grapes (sugar, color, aroma), the specificity and the typicality of the wines. Climate suitability for wine production was studied during a long period of time, between 2000 and 2018, in our experimental vineyards Tarnave and Murfatlar located inRomania, that integrates the influence of temperature and precipitation. The significant impact of climate change on viticulture requires in-depth studies of its consequences, in order to identify adaptation measures. The study allows in depth analysis from of the shifts caused by climate change in the wine areas, constituting a support for developing strategies of adaptation to the new climatic context. The study from the last eighteen years show a tendency to increase all the temperature-dependent climatic indices during the growing period of the grapes, with a large variation of the absolute minimum temperatures in winter, which suggests a change towards an increased thermal amplitude between summer and winter temperatures in certain years.